Fits Like a Glove: Rapid and Reliable Hand Shape Personalization - Tan, David Joseph; Cashman, Tom; Taylor, Jonathan; Fitzgibbon, Andrew; Tarlow, Daniel; Khamis, Sameh; Izadi, Shahram; Shotton, Jamie (IEEE Conference on Computer Vision and Pattern Recognition, 2016)
We present a fast, practical method for personalizing a hand shape basis to an individual user’s detailed hand shape using only a small set of depth images. To achieve this, we minimize an energy based on a sum of render-and-compare cost functions called the golden energy. However, this energy is only piecewise continuous, due to pixels crossing occlusion boundaries, and is therefore not obviously amenable to efﬁcient gradient-based optimization. A key insight is that the energy is the combination of a smooth low-frequency function with a high-frequency, low-amplitude, piecewise continuous function. A central ﬁnite difference approximation with a suitable step size can therefore jump over the discontinuities to obtain a good approximation to the energy’s low-frequency behavior, allowing efﬁcient gradient-based optimization. Experimental results quantitatively demonstrate for the ﬁrst time that detailed personalized models improve the accuracy of hand tracking and achieve competitive results in both tracking and model registration.